Manuel Rivero Collada. Negocios y política en Puebla, 1897-1916 - Gamboa Ojeda, Leticia (El Colegio de México, A.C., 1999)
This text describes the economic trajectory and changing political position of one of Puebla's leading entrepreneurs. This skillful businessman, was born in Asturias and emigrated from Seville to Mexico. He had and outstanding participation in agriculture, textile industries, and banking; with interests set beyond the limits of his state, he also influenced local politics during the last years of Díaz's government and durign those of Madero and Huerta. His high economic position, his leading role among Puebla employers and among the members of the Spanish  community and, above all, his activism against  the revolutionary movement made him the main target of popular hostility, spurred by the triumph of Carranza and expressed in a brief but strong wave of hispanophobia. His definitive return to Spain was the price this businessman had to pay for the great privileges he enjoyed.